How to make your research open access: options, tools, and supports - Hall, Robyn (My University, 2025)
Celebrate International Open Access Week by joining Scholarly Communications Librarian Robyn Hall for a session on sharing your research more widely. Learn practical strategies for making your publications freely available online, including selecting journals and repositories with open access options, accessing funding support, meeting research funder requirements, and navigating copyright with confidence. Participants will leave with tools and insights to easily enhance the visibility and impact of their work.
Presented on October 21, 2025 at MacEwan University in Edmonton, Alberta.
Keywords: open access; open access week; academic publishing; academic journals